Republic of Fiji : 2011 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2012)
This 2011 Article IV Consultation reports that Fiji's economic outlook appears stable, but there are downside risks related to the political situation, structural weaknesses, and the global environment. The 2012 budget has proposed much-needed fiscal consolidation, though marginal income tax rate reductions will make it difficult to achieve deficit targets. Monetary policy is accommodative, given the currently benign inflation outlook, but continued vigilance against future inflationary pressure is critical, and credit growth targets should be avoided.